PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA UNTUK PEMBUATAN ECO-ENZYME - Efi Nikmatu Sholihah; Dewi Ratna Nurhayati; Nur Wahyuti (LPPI UMN AL WASHLIYAH, 2025)
Waste is a complex societal problem. The current waste management paradigm has resulted in piles of waste in various areas and poses a threat of fire and health problems for the community. Existing waste management must be carried out wisely, including separating organic and inorganic waste and utilizing organic waste that can be converted into eco-enzymes. The purpose of this community service activity is to help the community manage organic waste at home so as not to add to the environmental waste pile. Community Service Activities were carried out at the PKK of Suruh Pabrik Village, RT/RW 03/02, Jatisobo, Polokarto, Sukoharjo, starting from May-August 2025, with 30 participants. The community service activities consisted of providing training to PKK women in Suruh Pabrik Village. The community service activities carried out by the target community have optimized the use of organic waste at home for processing into eco-enzymes, the results of which are used for floor cleaners and as organic liquid fertilizers for plants in the yard. The success rate of this community service activity reached 66.67%.